Increases in Language Input are Sustained among Mothers of Low SES: Evidence from a Randomized Controlled Trial. - Leung, Christy Y.Y.; Trinidad, Jose Eos; Suskind, Dana L. (Parenting: Science & Practice)
Objective. This randomized controlled trial examined whether the quantity and quality of maternal language input were increased through the 3Ts Home Visiting (3Ts-HV) intervention early in toddlerhood and whether increases in maternal language input were sustained over time among families of low SES, controlling for maternal education level, language skill, depressive symptoms, family adversity, child age, child language skills, and the length of recording. Design. 149 mother-toddler dyads of low SES were randomized to receive either the 3Ts-HV intervention (n = 76) or Healthy Lifestyle control (n = 73) curriculum from 14 to 20 months. Both quantity (tokens) and quality (lexical diversity, syntactic complexity, and use of complex sentences and wh-questions) of maternal language input were assessed at 14, 20, 26, 32, and 38 months. Hierarchical linear models were estimated to compare maternal language input between groups over time. Growth trajectories were modeled during the post-curriculum period alone, controlling for baseline maternal language input. Results. Intervention mothers had significantly larger increases in both quantity and quality of language input than Control mothers at 20 months. Intervention mothers' increases in both quantity and quality of language input were sustained at 26, 32, and 38 months. Conclusions. Language input can be promoted early in toddlerhood and sustained over time among families facing socioeconomic disadvantages. Fostering sustainable increases in maternal language behaviors with very young children among families of low SES is a critical first step in addressing early language input disparities.